The Steep Road of Land Law Dualism in Indonesia: Living Law VS Positive Law - Saharuddin; Sri Winarsi; Suardi Rais; Muhammad Ilham Arisaputra (Universitas Airlangga, 2026)
This research analyzes and formulates solutions to the problem of land law dualism in Indonesia which is characterized by the conflict between customary law (living law) and positive law (positive law). This dualism has created tensions between the recognition of indigenous peoples' rights to land and the state's authority to regulate the control and use of land, resulting in legal uncertainty, overlapping arrangements, and protracted agrarian conflicts. This research uses normative legal research methods with a focus on literature studies, examining primary legal materials such as the 1960 Basic Agrarian Law, the 1945 Constitution, and land-related regulations; secondary legal materials in the form of scientific literature, legal journals, research results, and the views of experts; and tertiary legal materials in the form of legal dictionaries, encyclopedias, and other supporting references. The approaches used include a historical approach to trace the roots of land law dualism since the colonial era, a conceptual approach to examine the theory of customary law and positive law, a legislative approach to analyze applicable legal norms, and a case approach through the study of land practices in Gorontalo, the Special Region of Yogyakarta, and Papua. The results of the study show the need for the integration of customary law into the national land law system through strengthening the position of customary law as a legitimate source of land law, the establishment of laws on indigenous peoples, and the preparation of regional regulations in areas that still have indigenous communities. This effort is expected to end the dualism of land law and create legal certainty that is in line with local values.